Controle mpc robusto com anti-windup aplicado a sistemas lpv e ltv baseado no algoritmo quasi-min-max com relaxação em lmis - Rego, Rosana Cibely Batista (2019)
This dissertation proposes a new technique to address constrained robust model predictive control (MPC) scheme combined with anti-windup compensator for linear parameter varying (LPV) and linear time-varying (LTV) systems based on a quasi-min-max algorithm with Linear Maxtrix Inequalities (LMI) relaxation. The approach is based on the use of several Lyapunov functions with each one corresponding to a different vertex of the polytopic system modeling. The main advantage of this new approach is the reduced conservativeness compared with others wellknown control techniques. The approach involves an offline design of a robust state observer for LPV and LTV systems with an online MPC algorithm. Also is proposed an offline MPC algorithm based on stabilizing invariant ellipsoids. A numerical example for a LPV system is used to validate the efficiency of the proposed approach. And in the end, the proposed techniques are applied to the LTV boost converter plant showing the good performance of the developed controller for both LPV and LTV systems